Enterovirus D68 circulation between 2014 and 2022 in Slovenian children - Uršič, Tina; Jevšnik Virant, Monika; Kogoj, Rok; Krivec, Uros; Prusnik, Joanna; Mramor, Minca; Lovšin, Sara; Petrovec, Miroslav (Frontiers in Virology, 2024)
Introduction: Enterovirus D68 belongs to the Picornaviridae family, genus Enterovirus. It is mostly known as a respiratory virus causing respiratory tract infections, but it is also rarely associated with a variety of central nervous system complications, with acute flaccid myelitis being reported most frequently. This study assesses the incidence, seasonality, clinical presentation, and molecular epidemiology of the EV-D68 strain in EV-positive children hospitalized between 2014 and 2022 at the largest pediatric medical center in Slovenia.Methods: EV-D68 was detected using specific rtRTqRT-PCR, whereas partial VP1 sequences were obtained with Sanger sequencing, and further analyzed phylogenetic analysis was obtained with Sanger sequencing by using the software CLC Main Workbench version 7 and MEGA version X. Results: EV-D68 was detected in 154 out of 1,145 (13.4%) EV-positive children. In the two epidemic years, 2014 and 2016, EV-D68 was most frequently detected in the summer and early autumn, peaking in September. The median age of EV-D68-infected children was 3 years (IQR 1-3 years), with a female: male ratio of 1:1.17. Rhinorrhea was present in 74.0% of children, respiratory distress in 82.5%, and hypoxemia requiring supplemental oxygen in 44.1%. Out of 154 patients, 80.0% were hospitalized, with a median stay of 2 days. Lower respiratory tract infection was observed in 89.0% of EV-D68-positive patients, with bronchitis and bronchiolitis being most frequently diagnosed. No central nervous system manifestations of EV-D68 infection were observed in the study cohort. Phylogenetic analysis of partial VP1 sequences of EV-D68 revealed close similarity to the EV-D68 variants that were circulating in other European countries in these years.Discussion: Slovenia faced two EV-D68 epidemics in 2014 and 2016; however, after 2016 only nine more cases were detected until the end of the study period. Based on the results of this study, EV-D68 was a frequent cause of lower respiratory tract infection among EV-positive patients. However, none of the patients we studied needed ICU treatment, and none developed acute flaccid paralysis. Our results indicate that EV-D68 is not present constantly, and so additional monitoring studies should be conducted in the future to better understand the implications of this EV type in human disease.